Faktor - Faktor Yang Mempengaruhi Kejadian Anemia pada Ibu Hamil Trimester III Di PMB Kunti Sari Lubis Kec. Perbaungan Tahun 2023 - Fitriani Fitriani; Basaria Manurung; Diah Pitaloka (Jurnal Ventilator, 2023)
Maternal Mortality Rate (MMR) is one indicator to see the success of maternal health efforts. MMR is the ratio of maternal deaths during pregnancy, childbirth and postpartum which are caused by pregnancy, childbirth and postpartum or its management but not due to other causes such as accidents for every 100,000 live births. This research aims to analyze the factors that influence the incidence of anemia in Third Trimester Pregnant Women at PMB Kunti Sari Lubis District. Perbauangan 2023. The type of research used is an analytical survey with a cross sectional approach. The population is all pregnant women in the third trimester of PMB Kunti Sari Lubis Kec. Perbauangan in 2023 and the sample in this study was 48 people. The data analysis technique used chi square. Based on statistical tests, the results obtained were p = 0.001 < 0.05, which can be interpreted that there is an influence between maternal age and the incidence of anemia in third trimester pregnant women. . p value = 0.021 < 0.05, which means that there is an influence between maternal education and the incidence of anemia in third trimester pregnant women. p value = 0.010 < 0.05, which means that there is an influence between maternal knowledge and the incidence of anemia in third trimester pregnant women. p value = 0.038 < 0.05, which means that there is an influence between maternal parity and the incidence of anemia in third trimester pregnant women.